Multiple factors on driving load in mountain area at night based on factor analysis. - Hao Li; Heng Jiang; Jiabao Yang (PLoS ONE)
Different driving environments may lead to increased mental workload and fatigue among drivers, consequently diminishing driving safety. To investigate the impact of various factors on drivers' driving load, this study approaches the issue from three perspectives: external weather environment, road driving environment, and in-vehicle driving environment. Through the experimental modeling of the mountainous road section of Provincial Highway S208 in Chongyang County, Xianning City, and employing simulated driving experiments, various factor combinations were designed to investigate the visual characteristics of drivers. Through factor analysis, a comprehensive examination is conducted on four visual indicators: the rate of change in pupil area, fixation duration, saccade velocity, and saccade angle, to explore the patterns of influence exerted by these factors on the driving load of drivers. The evaluation results of driving workload indicate that the degree of driver distraction decreases when the plant spacing is set at 6 meters and the type of road traffic auxiliary facilities is configured to two. When the traffic flow on the road is zero and no driving sub-mission are present, the driver experiences the minimum level of workload. The findings of this study provide robust theoretical support for nighttime mountain driving safety, contributing to the in-depth exploration of traffic safety theories.